Development of implicit and explicit attentional modulation of the processing of social cues conveyed by faces and bodies in children and adolescents - Oldrati, Viola; Bardoni, Alessandra; Poggi, Geraldina; Urgesi, Cosimo (Frontiers in Psychology, 2023)
Emotions and sex of other people shape the way we interact in social environments. The influence of these dimensions on cognitive processing is recognized as a highly conditional phenomenon. While much of researches on the topic focused on adults, less evidence is available for the pediatric population. This study aimed at examining the development of the modulation of attention control on emotion and sex processing using facial and body expressions in children and adolescents (8–16 years old). In Experiment 1a, participants performed a Flanker task (probing space-based attention) in which they had to indicate either the emotion (happy/fearful) or the sex of the target stimulus while ignoring the distracting stimuli at the side. We found evidence for intrusion of the sex, but not emotion, of the stimuli during both sex and emotion recognition tasks, thus both at an explicit (i.e., task relevant) and implicit (i.e., task irrelevant) level. A control experiment consisting of an emotional Flanker task confirmed that, in contrast with previous findings in adults, emotion did not modulate attention control in children and adolescents even when task relevant (Experiment 1b). In Experiment 2 participants performed a same-or-different judgment task (probing feature-based attention) in which they indicated whether the central stimulus matched the lateral ones for emotion or sex. Results showed that emotional features exerted an implicit influence during sex judgements; likewise, sex features intruded on the processing of both faces and bodies during emotion judgments. Finally, Experiment 3 explored the development of the explicit attention modulation exerted by the sex dimension on the processing of faces and bodies. To this aim, participants performed a Flanker task in which they were asked to recognize the sex of faces and bodies. The results indicated that, while younger participants showed a task-relevant influence of sexual features when processing faces, older participants showed such influence when processing bodies. These findings point to a greater attentional modulation exerted by sex, as compared to emotion, during social processing in children and adolescents and suggest a developmental trend of the saliency of facial and bodily cues for the perception of others’ sex.